Economic Policy of Renewable Energy: Development of Marine Current Energy in Madura Straits, Indonesia - Firdaus, Adil M.; Kusumastanto, Tridoyo; Nurjaya, I Wayan (Coastal and Ocean Journal (COJ), 2024)
The depletion of fossil resources and environmental degradation caused by conventional oil and gas exploitation highlight the urgency for renewable energy adoption to achieve sustainable development. Marine current energy offers a promising alternative, yet its economic feasibility remains insufficiently studied. The study aims to analyze the economic potential of marine currents energy and policy development as a source of renewable energy by developing of power plant in Madura Strait, East Java Province, Indonesia. The analysis methods used in this study were technical feasibility, econometric analysis, cost-benefit analysis, input-output model and policy analysis. Results showed that Madura Strait has sufficient resource potential to produce marine current energy, consumers’ income and KWh used are significant parameters in using marine current energy, the marine currents energy power plant development is financially feasible to be developed for at least 3 units (30 kW) or more with NPV of USD 57,010; Net B/C 1.57 and IRR 8% for 10 years investment period. Development of the power plant 3MW marine current energy will increase 0,02% of gross regional domestic product. Policy analysis using the Analytic Hierarchy Process (AHP) identifies regional infrastructure development, including coastal spatial planning, as the top policy priority.